Dynamic genome-wide gene expression and immune cell composition in the developing human placenta. (June 2022) - Suryawanshi, Hemant; Max, Klaas; Bogardus, Kimberly A.; Sopeyin, Anuoluwapo; Chang, Michael S.; Morozov, Pavel; Castano, Paula M.; Tuschl, Thomas; Williams, Zev
Abstract: Despite the central role of the placenta in supporting a pregnancy, relatively little is known about transcriptomic and immune-cell changes that occur across gestation. To generate a reference gene expression map of first (T1), second (T2) and third (T3) trimester human placenta, and assess differences in transcriptome in maternal versus fetal side tissues sections of full-term placenta, we performed RNA-Seq analysis on 64 biopsy samples from 18 placentas across all three gestations. We identified 1120 differentially expressed genes in placenta tissues from T1 and T3 samples using a generalized linear model within DESeq2. In total, 411 and 709 genes were positively associated with T1 and T3 placenta, respectively. Comparison of the top 200 differentially expressed genes in the T1 placenta with T3 showed that most of the top enriched biological processes were related to cell division and proliferation. T1 and T2 tissues shared expression of fibroblast-specific COL6A2, HGF, and SPP1 genes. In T3 samples, the expression of genes relating to vasculature development and regulation were highly enriched. Monocytes and NK cell population increased in T3 compared to T1 and T2, whereas Hofbauer cell proportion expanded significantly in T2 and then decreased in T3 samples. There were no significant gene expression differences in the maternal vs. fetal side in T3 placentas. Gene expression patterns shift temporally across trimesters but not spatially across the placenta, at least at the resolution of the biopsy samples. The genes and gene set we identified here represent a valuable resource for studying pathology in pregnancy-related disorders. Highlights: A comprehensive transcriptome is presented of human placenta across three trimesters. 1120 genes were differentially expressed in first (T1) and third (T3) trimester placenta samples. T1: Enrichment of cell division and proliferation processes; T3: Vasculature development and regulation processes upregulated. No significant gene expression differences in the maternal vs. fetal side in T3 placentas.